Justification of the preliminary enzymatic treatment of berries of dogwood, black elderberry, hawthorn, barberry and raspberry, grown in the territory of the Republic of Azerbaijan - Maharramova, Sevinj; Kazimova, Ilhama; Maharramov, Mikail (Technology audit and production reserves, 2026)
The research shows the results of the effect of preliminary enzymatic treatment of dogwood berries, black elderberry, hawthorn, barberry and raspberry on juice yield and extraction of valuable chemical compounds and nutrients into juice. The objects of the research were the technology for enzymatic extraction of dogwood berries, black elderberries, hawthorn berries, barberries, and raspberries. Enzyme preparations with pectolytic and gluconolytic activity were also investigated. The enzymes included Pectinex BE XXL, Pectinex Yieldash Extra, Amylase AG 300 L, and Fructozym P. Additional preparations used in the research were Rapidaza CR, Bryuzaym BGX, Laminex Super, Selloviridin Q20X, Sellokyuks-A Extra, and Enzerzim XT. The experiment used modern photometric, thermogravimetric, refractometric, potentiometric, chromatographic and other methods of analysis. It was established that the use of a composition of enzyme preparations with pectolytic and glucanolytic action Pectinex BE XXL, Amylase AG 300 L, Rapidaza CR, Sellokyuks-A contributes to an increase in the yield of unclarified juices by an average of 6.8–9.4% compared to the control samples. In this case, the most effective are the use of Fructosym P, Pectinex BE XXL and Amylase AG300L, and when using multienzyme complexes, MFK-I and MFK-II turned out to be more effective, each consisting of a mixture of two enzymes, the juice yield increased by an average of 11.0–14.4% or 1.19–1.29 times compared to the control. The use of the enzyme preparation composition allows to increase the yield of valuable natural components and functional food ingredients in the juice – total sugars by 1.05–1.23 times, organic acids by 1.04–1.24 times, pectin substances by 1.06–1.31 times, ash substances by 1.19–1.33 times, vitamin C by 1.18–1.38 times. The extraction of natural antioxidants and preservatives increases the nutritional value of the juice and improves its technological properties.